Organophosphate and pyrethroid resistances in the tomato leaf miner Tuta absoluta (Lepidoptera: Gelechiidae) from Iran. (12th September 2017) - Zibaee, I.; Mahmood, K.; Esmaeily, M.; Bandani, A. R.; Kristensen, M.
Abstract: The tomato leafminer, Tuta absoluta (Meyrich) (Lepidoptera: Gelechiidae), is a serious pest of tomato crops worldwide. The intensive use of chemical pesticides to control it has led to the selection of resistant populations. This study investigated the resistance of T. absoluta populations to pyrethroid and the organophosphate insecticides from ten regions of Iran. The resistance ratios at LC50 for chlorpyrifos and diazinon varied among populations from 4.3 to 12 and from 1.4 to 9.0, respectively. The resistance ratios of the pyrethroids cypermethrin, deltamethrin and permethrin varied from 1.3 to 3.7, 2.7 to 13 and 1.2 to 4.3, respectively. Inclusion of synergists in toxicological bioassays and the variation observed in the activity of esterases, glutathione S ‐ transferase and cytochrome P450‐dependent monooxygenase suggest the existence of metabolically based resistance. Esterase and P450 biochemical assays were positively correlated with deltamethrin, and cypermethrin tolerance and diazinon tolerance correlated with esterase activity. The genes encoding the organophosphate and pyrethroid target sites acetylcholinesterase ( ace 1) and sodium channel ( kdr ) were partly sequenced. The genotyping revealed mutations in high frequencies in all populations leading to an A201S substitution in ace1 and three substitutions in the sodium channel gene L1014F, M918T, T929I. In summary, our results indicate the presence of organophosphate and pyrethroid resistance in Iranian T. absoluta populations with involvement of both detoxification enzymes and target site alterations. Most likely the populations of T. absoluta imported to Iran were resistant upon arrival.